Electromagnetic field simulation and crack analysis of electromagnetic forming of Magnesium alloy tube - Wang,Z. F. (2011)
The AZ31 magnesium alloy tube was used for electromagnetic forming experiment of three kinds of input voltages. The stress-strain state of tube forming was analyzed. It was shown that the cause of oblique crack of tube was σr of axial inhomogeneous distribution and σz, and the cause of longitudinal crack was σr and σè of inhomogeneous distribution in circumferential direction. Moreover, the electromagnetic field and force field during electromagnetic forming was simulated by ANSYS software. The experiment proved the simulation result.